Characterization of exopolysaccharide and ropy capsular polysaccharide formation by Weissella. (April 2015) - Malang, Saskia Katharina; Maina, Ndegwa Henry; Schwab, Clarissa; Tenkanen, Maija; Lacroix, Christophe
Abstract: With their broad functional properties, lactic acid bacteria derived high molar mass exopolysaccharides (EPS) and oligosaccharides are of great interest for food, medical and pharmaceutical industry. EPS formation by 123 strains of Weissella cibaria and Weissella confusa, was evaluated. Dextran formation from sucrose was observed for all tested strains while 18 strains produced fructan in addition to dextran. Six isolates synthesized a highly ropy polymer from glucose associated with the formation of a cell-bound, capsular polysaccharide (CPS) composed of glucose, O-acetyl groups and two unidentified monomer components. The soluble EPSs of nine strains were identified as low α-1, 3-branched dextran, levan and inulin type polymers using NMR. In addition to glucan and fructan, W. confusa produced gluco- and fructooligosaccharides. Partial dextransucrase and fructansucrase sequences were characterized in the selected Weissella strains. Our study reports the first structural characterization of fructan type EPS from Weissella as well as the first Weissella strain producing inulin. Production of more than one EPS-type by single strains may have high potential for development of applications combining EPS technological and nutritional benefits. Highlights: Weissella synthesize structurally and compositionally diverse exopolysaccharides. Dextran, levan and inulin type fructans of Weissella identified by NMR-spectroscopy. Weissella produce cell associated ropy polymers. Weissella strains can concomitantly produce more than one type of exopolysaccharide.